The intervention of educational big data analytics for an effective eLearning experience : the case of Zimbabwe’s Higher and Tertiary Education - Mugoniwa, Beauty; Tsimba, Gerald; Mutembedza, Amanda (IST-Africa Institute and IIMC, 2022)
Today, virtually every operation is affected by digitalization the world over. As a result, it is of utmost importance for every organization to check and conform to the updated digital solutions. This paper sought to investigate whether Zimbabwean higher and tertiary education has adopted Educational Big Data (EBD) taking advantage of eLearning platforms. It also aims to determine challenges militating against the adoption educational data analytics, hence, proffering strategies for the full implementation of EBD. The study pursued a qualitative research methodology based on a multiple case study design strategy. The study identified challenges which included lack of infrastructure, skills and related resources; lack of government will and weak institutional investment strategies. With that in mind, there was no substantial evidence that proved the existence of EBD from the selected five tertiary intuitions involving lecturers and administrators as participants. Hence, the study proposed an EBD strategy implementation, execution and control model.